The Influence of Electronic Word of Mouth and Consumer Involvement on Product Purchasing Decisions at Supplier CV.Adijaya, West Bandung District - Andri Asoka Sidantara Rosadi; Rizki Tedja Sukma (PT FORMOSA CENDEKIA GLOBAL, 2023)
CV.Adijaya Supplier company is engaged in the sale of imported and local food raw materials for the needs of hotels, restaurants and bakeries abbreviated as horecaba since 2012 until now. The company sells goods from importers for resale both for sale to individuals and large parties. The goods sold are imported goods from abroad and within the country. This study is designed to determine, both partially and simultaneously on purchasing decisions, how much influence Electronic Word Of Mouth and consumer involvement have in influencing purchasing decisions. Descriptive methods and associative methods will be applied to the research conducted in this study. The sample in this study amounted to 163 respondents. Sampling using Probability Sampling. Testing the validation and reliability of research instruments is also carried out in the analysis method using a number of linear regression analyses. Based on the results of the study, there is an influence of the external variables Electronic Word of Mouth and Consumer Engagement on the endogenous variables of Purchasing Decisions partially and simultaneously. Other factors that have not been studied in this study explain the magnitude of the influence of the work environment and education on performance, namely R2 x 100%7 of 66.7.7% and 33.3% respectively